The book thief - Zusak, Markus (New York : Alfred A. Knopf, 2016)
Trying to make sense of the horrors of World War II, Death relates the story of Liesel--a young German girl whose book-stealing and story-telling talents help sustain her family and the Jewish man they are hiding, as well as their neighbors.
Keywords: DEATH -- FICTION